Peran Badan Permusyawaratan Desa (PBD) dalam Menyerap Aspirasi Masyarakat dalam Perencanaan Pembangunan Desa di Desa Wandanpuro Bululawang Malang - Rohman Kusmayadi, Rudy Catur (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2022)
The successful implementation of community development is very dependent on the role of government and  society. Without involving the community, the village government will not be able to achieve optimal development results. One of the functions of the Village Consultative Body (BPD) is to channel community aspirations in village development planning. Because it is from community participation that the direction of village development is determined. Community participation will be higher if there is encouragement and appeal from the Village Consultative Body (BPD) in implementing development. The role of BPD is very important in absorbing and accommodating people's aspirations. In this study using descriptive qualitative. This type of research is field research, namely conducting research on the role of the Village Consultative Body (BPD) in absorbing community aspirations in village development planning in Wandanpuro Village, Bululawang District. The results of the study show that the role of the Village Consultative Body (BPD) is expected in absorbing community aspirations not only in formal events such as Pra-Musdes/Musdus and Musdes, but is able to take a more approach to the community to accommodate aspirations in order to foster community aspirations and participation in development planning , such as "jagongan", "coffee together", and attending religious activities and cultural meetings in the village area. It is hoped that the Village Consultative Body (BPD) will also seek new strategies to absorb community aspirations in development planning and further enhance hamlet deliberation activities by narrowing their scope, for example at the RT and RW levels. Keywords: role; participation; aspirations; development; planning